2004
DOI: 10.1038/sj.ejcn.1602077
|View full text |Cite
|
Sign up to set email alerts
|

Lupin kernel fibre-enriched foods beneficially modify serum lipids in men

Abstract: Objective: To examine the effect of a diet containing a novel legume food ingredient, Australian sweet lupin (Lupinus angustifolius) kernel fibre (LKFibre), compared to a control diet without the addition of LKFibre, on serum lipids in men. Design: Randomized crossover dietary intervention study. Setting: Melbourne, Australia -Free-living men. Subjects: A total of 38 healthy males between the ages of 24 and 64 y completed the intervention. Intervention: Subjects consumed an LKFibre and a control diet for 1 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 48 publications
3
66
1
3
Order By: Relevance
“…Isolation and purification of lupin kernel fibre can result in a higher ratio of soluble to insoluble fibre and higher viscosity and water-binding capacity than fibre naturally present in LKF. 46 In addition, the increase in lupin kernel fibre intake in the study by Hall et al 25 was about twice of that in our study.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…Isolation and purification of lupin kernel fibre can result in a higher ratio of soluble to insoluble fibre and higher viscosity and water-binding capacity than fibre naturally present in LKF. 46 In addition, the increase in lupin kernel fibre intake in the study by Hall et al 25 was about twice of that in our study.…”
Section: Discussionsupporting
confidence: 46%
“…24 In humans, a lupin fibre isolate, providing an additional 17-30 g per day of dietary fibre, reduced total and low-density lipoprotein (LDL)-cholesterol concentrations by B5%. 25 Results of acute studies also suggest the potential for benefit of lupin-enriched foods on blood glucose metabolism. 2,26 We have previously shown that consumption of LKF-enriched bread significantly reduced postprandial glucose and insulin in comparison with matching energy from white bread.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Both studies produced significant decreases of total and LDL-C, but the changes were much less favourable in the old study (R. S. Hall, Johnson, Baxter, & Ball, 2005), where the changes in total cholesterol and LDL-C were -0.22 mmol/L and -0.19 mmol/L, respectively, than in the recent one based on subjects with higher baseline cholesterol levels , where the changes in total cholesterol and LDL-C were -0.42 mmol/L and -0.33 mmol/L, respectively. In the latter study, a significant decrease of blood pressure was also observed (section 4.2.)…”
Section: Human Studiesmentioning
confidence: 99%